PERBEDAAN HASIL BELAJAR MODEL BERBASIS MASALAH DENGAN PENUGASAN DALAM MATERI IPS UNTUK MENUMBUHKAN KEPEDULIAN KEPEDULIAN TERHADAP LINGKUNGAN (GREEN BEHAVIOR) : Studi Eksperimen di Kelas 8 SMP Negeri 35 Kota Bandung - Suharjani, Neni (2014)
Penelitian ini dilatarbelakangi oleh permasalahan dalam pembelajaran IPS tidak menumbuhkan kepedulian lingkungan (green behavior) peserta didik, padahal materi lingkungan hidup dan upaya penanggulangannya dalam pembangunan berkelanjutan merupakan salah satu materi pembelajaran yang dipelajari di kelas VIII semester ganjil. Tujuan penelitian ini untuk mengetahui perbedaan hasil belajar model pembelajaran berbasis masalah dengan model pembelajaran penugasan dapat meningkatkan pengetahuan, pemahaman untuk menumbuhkan kepedulian terhadap lingkungan. Penggunaan model pembelajaran berbasis masalah dan model pembelajaran penugasan mendorong peserta didik terlibat secara maksimal dengan seluruh kemampuannya untuk mencari dan menyelidiki dari suatu fenomena dengan sistematis, kritis, logis dan analitis, sehingga peserta didik dapat memecahkan masalah dan menerapkan dalam kehidupan sehari-hari. Subyek penelitian adalah peserta didik kelas VIII SMPN 35 Bandung yang berjumlah 114 orang. Dalam memperoleh data dan menjawab permasalahan penelitian, peneliti menerapkan penelitian eksperimen, pengumpulan data dan teknik tes (pre tes dan post tes). Jenis pengumpulan data penelitian dan teknik pengolahan data adalah validitas, reliabilitas, uji normalitas dan homogenitas serta uji-t dengan bantuan software SPSS program version 20. Hasil analisis data menunjukkan bahwa model pembelajaran berbasis masalah dan penugasan dapat meningkatkan pengetahuan dan pemahaman materi lingkungan, dimana dalam penerapannya peserta didik terlihat sudah mulai berperilaku membiasakan diri membuang sampah pada tempatnya. Kata kunci : Pembelajaran Berbasis Masalah, Pembelajaran Penugasan, Peduli Lingkungan (Green Behavior) This research's background was triggered by problem in the social sciences learning which does not increase learners' environmental attention (green behavior) although the material in environment and mitigation efforts in sustainable development is one of the learning material studied in Class VIII, odd semester. The purpose of this study is to determine the differences between Problem Based Learning Model outcomes and Assignment Based Learning model to improve knowledge , and to foster understanding environmental concerns. The use of Problem -based Learning model and Assignment Based Learning model in encouraging learners to involve thoroughly with all their abilities to locate and to investigate the phenomenon of a systematicly, critically, logically and analytically, so that learners can solve problems and apply in everyday life. The subjects were Grade VIII SMP 35 Bandung , in about 114 students. In obtaining the data and answering the research problem, the writer applied experimental research,data collection and technical tests ( pre-test and post- test ). The types of research data collection and data processing techniques are validity, reliability, test for normality and homogeneity as well as the t-test with the help of SPSS software program version 20. The results of data analysis presents that problem-based learning assignment based learning model can improve knowledge and understanding of the material environment, where the application looks learners have started to behave to get used to dispose of waste in place. Keywords: Problem Based Learning Model, Assignment Based Learning Model, Environment Attention (Green Behavior) This research's background was triggered by problem in the social sciences learning which does not increase learners' environmental attention (green behavior) although the material in environment and mitigation efforts in sustainable development is one of the learning material studied in Class VIII, odd semester. The purpose of this study is to determine the differences between Problem Based Learning Model outcomes and Assignment Based Learning model to improve knowledge , and to foster understanding environmental concerns. The use of Problem -based Learning model and Assignment Based Learning model in encouraging learners to involve thoroughly with all their abilities to locate and to investigate the phenomenon of a systematicly, critically, logically and analytically, so that learners can solve problems and apply in everyday life. The subjects were Grade VIII SMP 35 Bandung , in about 114 students. In obtaining the data and answering the research problem, the writer applied experimental research,data collection and technical tests ( pre-test and post- test ). The types of research data collection and data processing techniques are validity, reliability, test for normality and homogeneity as well as the t-test with the help of SPSS software program version 20. The results of data analysis presents that problem-based learning assignment based learning model can improve knowledge and understanding of the material environment, where the application looks learners have started to behave to get used to dispose of waste in place. Keywords: Problem Based Learning Model, Assignment Based Learning Model, Environment Attention (Green Behavior) This research's background was triggered by problem in the social sciences learning which does not increase learners' environmental attention (green behavior) although the material in environment and mitigation efforts in sustainable development is one of the learning material studied in Class VIII, odd semester. The purpose of this study is to determine the differences between Problem Based Learning Model outcomes and Assignment Based Learning model to improve knowledge , and to foster understanding environmental concerns. The use of Problem -based Learning model and Assignment Based Learning model in encouraging learners to involve thoroughly with all their abilities to locate and to investigate the phenomenon of a systematicly, critically, logically and analytically, so that learners can solve problems and apply in everyday life. The subjects were Grade VIII SMP 35 Bandung , in about 114 students. In obtaining the data and answering the research problem, the writer applied experimental research,data collection and technical tests ( pre-test and post- test ). The types of research data collection and data processing techniques are validity, reliability, test for normality and homogeneity as well as the t-test with the help of SPSS software program version 20. The results of data analysis presents that problem-based learning assignment based learning model can improve knowledge and understanding of the material environment, where the application looks learners have started to behave to get used to dispose of waste in place. Keywords: Problem Based Learning Model, Assignment Based Learning Model, Environment Attention (Green Behavior)